2011
DOI: 10.1093/abbs/gmr031
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex RT-PCR detection of <italic>Cucumber mosaic virus</italic> subgroups and <italic>Tobamoviruses</italic> infecting Tomato using 18S rRNA as an internal control

Abstract: A multiplex reverse-transcription polymerase chain reaction (RT-PCR) protocol was developed for simultaneous detection and discrimination of subgroups of Cucumber mosaic virus (CMV), including its satellite RNA, Tomato mosaic virus (ToMV) and Tobacco mosaic virus (TMV), using 18S rRNA as an internal control. Species-and subgroups-specific primers designed to differentiate CMV subgroups I and II, ToMV and TMV, were assessed using the cDNA clones of viral genomes, CMV satellite RNA and 18S rRNA gene from tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
(30 reference statements)
1
18
0
1
Order By: Relevance
“…Samsun using Tri-reagent (Sigma) and first-strand cDNA synthesis was performed using RevertAid M-MuLV reverse transcriptase according to the manufacturer's instructions (Fermentas UAB, Lithuania). First, CMV isolates were tested for the presence of satellite RNA and their classification in different subgroups was determined using specific primers as described previously (8). A DNA fragment with the expected size (about 600 bp) was amplified in all CMV isolates using subgroup I specific primers whereas no amplicon was obtained for CMV subgroup II or satellite RNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samsun using Tri-reagent (Sigma) and first-strand cDNA synthesis was performed using RevertAid M-MuLV reverse transcriptase according to the manufacturer's instructions (Fermentas UAB, Lithuania). First, CMV isolates were tested for the presence of satellite RNA and their classification in different subgroups was determined using specific primers as described previously (8). A DNA fragment with the expected size (about 600 bp) was amplified in all CMV isolates using subgroup I specific primers whereas no amplicon was obtained for CMV subgroup II or satellite RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Those in the Mediterranean could have been introduced recently from East Asia (1,7). Isolates of subgroups I and II can be identified using monoclonal antibodies, and isolates from subgroups IA, IB and II can be determined by reverse transcriptase polymerase chain reaction (RT-PCR) (8). Many studies on CMV in Iran have been limited to serological and biological detection.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR amplification conditions were initial denaturation at 95°C for 2 min, 35 cycles of 95°C for 30 s, annealing at the 50°C (CMV), 48°C (WMV-2), 47°C (ZYMV) and extension at 72°C for 1 min, with a final extension step at 72°C for 10 min. Also, CMV isolates were tested for the presence of different subgroups and satellite RNA using specific primers as described previously (Chen et al 2011). The RT-PCR product was isolated by excising the band from agarose gel and purified using Wizard PCR DNA purification system (Promega, USA) and were cloned into pGEM-T Easy vector (Promega Crop., Madison, WI) according to the manufacturer's Archives of Phytopathology and Plant Protection 5 recommendations.…”
Section: Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
“…The virus spreads in sap through vegetative propagation, mechanical means and environmental water (Mehle & Ravnikar, ). Enzyme‐linked immunosorbent‐assay (ELISA) (Bar‐Joseph & Salomon, ), Reverse transcription‐loop‐mediated isothermal amplification (RT‐LAMP) (Liu et al, ), and Reverse transcription PCR (RT‐PCR) (Chen et al, ) have already been reported for detection of this virus.…”
Section: Introductionmentioning
confidence: 99%